A crosstalk between chromatin remodeling and histone H3K4 methyltransferase complexes in endothelial cells regulates angiotensin II-induced cardiac hypertrophy. (May 2015) - Weng, Xinyu; Yu, Liming; Liang, Peng; Li, Luyang; Dai, Xin; Zhou, Bisheng; Wu, Xiaoyan; Xu, Huihui; Fang, Mingming; Chen, Qi; Xu, Yong
Abstract: Angiotensin II (Ang II) induces cardiac hypertrophy and fibrosis in part by stimulating endothelin (ET-1) transcription. The involvement of the epigenetic machinery in this process is largely undefined. In the present study, we examined the epigenetic maneuvering underlying cardiac hypertrophy and fibrosis following ET-1 transactivation by Ang II. In response to Ang II stimulation, core components of the mammalian chromatin remodeling complex (Brahma-related gene 1, or Brg1, and Brahma or Brm) and histone H3K4 methylation complex (Ash2, absent, small, or homeotic discs 2, or Ash2 and WD domain repeat 5, or Wdr5) were recruited to the ET-1 promoter region in endothelial cells. Over-expression of Brg1/Brm or Ash2/Wdr5 enhanced while depletion of Brg1/Brm or Ash2/Wdr5 attenuated Ang II-induced ET-1 transactivation. Endothelial-specific knockdown of Brg1/Brm or Ash2/Wdr5 ameliorated cardiac hypertrophy both in vitro and in vivo . More important, Brg1/Brm interacted with Ash2/Wdr5 on the ET-1 promoter to catalyze H3K4 methylation. The crosstalk between Brg11/Brm and Ash2/Wdr5 was mediated by myocardin-related transcription factor A (MRTF-A). In conclusion, our data have unveiled an epigenetic complex that links ET-1 transactivation in endothelial cells to Ang II-induced cardiac hypertrophy and fibrosis. Highlights: Ang II recruits BRG1 and BRM to the ET-1 promoter region to activate transcription. Endothelial deletion of BRG1/BRM attenuates Ang II-induced hypertrophy in mice. Ang II recruits ASH2 and WDR5 to the ET-1 promoter region to activate transcription. Endothelial deletion of ASH2 or WDR5 attenuates Ang II-induced hypertrophy in mice. MRTF-A mediates the crosstalk between BRG1 and ASH2 on the ET-1 promoter.